(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The research aims to identify the level of effectiveness of the teaching practices of science and mathematics teachers in light of the national framework for future skills in Omani schools. To achieve the objectives of the study, the researchers used the descriptive approach, as he designed a note card consisting of (30) phrases distributed on three axes: basic skills, practical skills, and technical skills. After verifying the validity and reliability of the tools, they were applied to a sample of (116) teachers. The results of the research revealed that the level of effectiveness of the teaching practices of mathematics teachers has recorded a medium degree with a mean (3.05). The results also indicated that there are statistically significant differences at the level of significance among the averages of the effectiveness level due to gender variables in favor of females. Additionally, the study revealed there are no statistically significant differences among the averages of the effectiveness level due to the variables of the educational stage. The researchers recommended the need to adopt a strategy to develop teaching practices in light of future skills and to employ training in raising the performance level of science and mathematics teachers.